Are all police officers equally triggered?: A test of the interaction between moral support for the use of force and exposure to provocation - Noppe, J. (Policing and society, 2018)
The aim of this study is to investigate the interplay between moral support for the use of force and exposure to provocative settings in explaining individual differences in self-reported use of force by the police. In the police literature, the relationship between a suspect’s behaviour and police use of force has often been scrutinised. Those studies conclude that a suspect’s resistance is a key predictor of police use of force. In this article, we start from a different theoretical approach towards the study of police use of force based on one of the main principles of Wikström’s situational action theory (SAT). We examine the extent to which a police officer’s self-reported use of force can be explained by the main and interactive effects of moral support for the use of force and exposure to provocative settings. Our findings provide some evidence for SAT, and indicate that the effect of exposure to provocative settings is especially strong among police officers who score highly on moral support for the use of force.